Usaha Meningkatkan Penjualan Melalui Strategi Pemasaran - Arinastuti, Arinastuti; Harsuti, Harsuti; Nirmala, Nirmala (WIKUACITYA: Jurnal Pengabdian Kepada Masyarakat, 2025)
The purpose of community service is to provide an understanding of knowledge about efforts to increase sales through marketing strategies and provide knowledge about business development A marketing strategy is a set of goals and objectives, policies and rules that guide a company's marketing efforts from time to time, at all levels and references and allocations, especially the company's response to the environment and competitive conditions that are always changing (Assauri, 2017). An example of a marketing strategy, business actors carry out partnership marketing (collaborating with other parties), collaborating with influencers, involving employees in introducing products and retaining customers. The target of this community service is the owner of the Three Brothers Mushroom UMKM Business in Kalikesur Village, Kedungbanteng District, Banyumas Regency The method used is the lecture method from the community service team or face-to-face and the provision of assistance with spinner tools and digital scales. With the help of these tools, the production results can be crispier, crunchier and savory and the appearance of the product is whiter in color. Digital scales are intended to weigh processed mushrooms with the appropriate weight, so that the scales are not approximate. Keywords: Sales Results, Marketing Strategy, Business Development